EUROPEAN PARLIAMENT’S POLITICAL PARTIES FAMILY: PRINCIPLES OF OPERATION AND IDEOLOGICAL SPECIFICS - Вархов, Г. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
This article explores the basic principles of operation of the European Parliament, his party structure at the beginning and at the present stage. Defined group of political parties that were formed after the last elections to the European Parliament. The influence of their activities on the policy of the European Union and the international arena in general.